Development and evaluation of reverse transcription loop-mediated isothermal amplification for rapid and real-time detection of Kyasanur forest disease virus. (November 2021) - Kumar, Jyoti S.; Yadav, Pragya D.; Shete, Anita M.; Majumdar, Triparna; Patil, Savita; Dash, Paban Kumar
Highlights: LAMP technology is isothermal and can be performed in dry bath. LAMP technology is simple, rapid, highly sensitive and cost effective. It can be use as point of care diagnostics. Results can be obtained within 1 h and interpreted by naked eye visualization. Abstract: Significance: Kyasanur forest disease (KFD), a re-emerging tick-borne viral disease, causes severe hemorrhagic fever in humans and nonhuman primates. KFD virus (KFDV) is a member of the genus Flavivirus . KFD is now increasingly reported outside its endemic zone in India. Rapid and specific detection of the KFDV plays a critical role in containment of the outbreak. The diagnosis of KFD currently relies on real-time RT-PCR, nested RT-PCR, end point RT-PCR, and serodiagnostic assay. These assays are tedious, time-consuming, and cannot be used as a routine screening platform. Objective: The present study was aimed to develop a one-step reverse transcription loop-mediated isothermal amplification (RT-LAMP) assay for molecular diagnosis of KFD. Design: The gene amplification reaction was accomplished by incubation at a constant temperature of 63 °C for 60 min. Results: The limit of detection of RT-LAMP assay was 10 copies. KFD RT-LAMP assay was successfully evaluated with diverse host samples including humans, monkeys, and tick. The assay correctly picked up different KFD isolates indicating its applicability for divergent strains. Comparative evaluation of RT-LAMP assay with quantitative TaqMan real-time RT-PCR revealed 100% concordance. No cross-reaction with related flavi and other hemorrhagic fever viruses was observed, indicating its high specificity. Conclusion and relevance: The RT-LAMP test developed in this study will serve as a rapid, sensitive alternate detection method for KFDV infection and would be useful for high throughput screening of clinical samples in resource limited areas during outbreaks.